IRAK-M regulation and function in host defense and immune homeostasis - Leah L.N. Hubbard; Bethany B. Moore (MDPI AG, 2010)
Antigen presenting cells (APCs) of the innate immune system sense a wide range of pathogens via pattern recognition receptors (PRRs). Engagement of certain PRRs can induce production of pro-inflammatory mediators that facilitate effective clearance of pathogen. Toll-like receptors (TLRs) are a well described group of PRRs that belong to the TLR/Interleukin-1 receptor (IL-1R) superfamily. However, TLR/IL-1R induction of pro-inflammatory mediators must be regulated to prevent excessive inflammation and tissue damage. One molecule of recent interest that is known to inhibit TLR/IL-1R signaling is interleukin-1 receptor associated kinase (IRAK)-M, also known as IRAK-3. IRAK-M is expressed in a number of immune and epithelial cells types, and through its inhibition of pro-inflammatory cytokine production, IRAK-M can regulate immune homeostasis and tolerance in a number of infectious and non-infectious diseases. Furthermore, use of IRAK-M deficient animals has increased our understanding of the importance of IRAK-M in regulating immune responsiveness to a variety of pathogens. Although IRAK-M expression is typically induced through TLR signaling, IRAK-M can also be expressed in response to various endogenous and exogenous soluble factors as well as cell surface and intracellular signaling molecules. This review will focus on clinical scenarios in which expression of IRAK-M is beneficial (as in early sepsis) and those situations where IRAK-M expression is harmful to the host (as in cancer and following bone marrow transplant). There is strong rationale for therapeutic targeting of IRAK-M for clinical benefit. However, effective targeting will require a greater understanding of the transcriptional regulation of this gene.